Epic Visions : Visuality in Greek and Latin Epic and its Reception. - Lovatt, Helen (Cambridge University Press, 2013)
A wide-ranging, interdisciplinary collection exploring different ways of visualising Greek and Roman epic in both ancient and modern culture.